2022
DOI: 10.32604/ijmhp.2022.021452
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disorders of the Indonesian People in the Early Stages of the COVID-19 Pandemic: Who is Vulnerable to Experiencing it?

Abstract: The extraordinary situation related to COVID-19 makes people worry about their health, family health, work, finances, and other daily activities. This condition can lead to social unrest, which has consequences for mental health problems. This study aims to determine the mental health consequences at the beginning of the COVID-19 pandemic in Indonesia. This is a cross-sectional study involving a target population aged 18 years and over who had access to electronic communication devices. An online questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Multiple variables have been discovered to be associated with mental health conditions during the COVID-19 pandemic. Previous histories of mental illness, chronic illness, and layoffs were the most substantial factors influencing anxiety and depression in the Indonesian community (Mubasyiroh et al, 2022). Additionally, other studies have indicated that young age, female gender, having low education, and low income are associated with mental health during the COVID-19 pandemic (Chekole & Abate, 2021;Nagasu et al, 2021;O'Connor et al, 2021).…”
Section: Factors Associated With Common Mental Disorders and The Pres...mentioning
confidence: 97%
See 1 more Smart Citation
“…Multiple variables have been discovered to be associated with mental health conditions during the COVID-19 pandemic. Previous histories of mental illness, chronic illness, and layoffs were the most substantial factors influencing anxiety and depression in the Indonesian community (Mubasyiroh et al, 2022). Additionally, other studies have indicated that young age, female gender, having low education, and low income are associated with mental health during the COVID-19 pandemic (Chekole & Abate, 2021;Nagasu et al, 2021;O'Connor et al, 2021).…”
Section: Factors Associated With Common Mental Disorders and The Pres...mentioning
confidence: 97%
“…A study in China reported that 35.1%, 20.1%, and 18.2% of the population experienced anxiety, depression, and poor sleep quality, respectively (Huang & Zhao, 2020). During Indonesia's first two months of the COVID-19 pandemic, 6.9% of the population experienced anxiety, and another 8.6% experienced depression (Mubasyiroh et al, 2022). Furthermore, another study conducted in Indonesia found that more than 20% of the general population experienced anxiety, while over 30% suffered from depression (Anindyajati et al, 2021;Izzatika et al, 2021).…”
Section: Factors Associated With Common Mental Disorders and The Pres...mentioning
confidence: 99%
“…Berdasarkan penelitian yang dilakukan oleh (Mubasyiroh, 2017), menunjukkan bahwa determinan dari gejala mental emosional pada pelajar SMP-SMA dengan usia terbanyak 13-15 tahun yaitu 7,33% pernah ingin bunuh diri, 40,75 merasakan kecemasan, 44,45% merasa kesepian, 60,17% yang mengalami gejala masalah mental emosional.…”
Section: Pendahuluanunclassified